Mesothelin versus Ca125 in Screening the Ovarian Malignancy - Meliana Jayasaputra; Freddy W Wagey; Max R Rarung (Indonesian Socety of Obstetrics and Gynecology, 2016)
Objective: To determine the sensitivity and specificity of mesothelin compared with Ca-125 as a tumor marker in predicting ovarian malignancy. Method: The cross sectional study design with diagnostic tests was conducted in 30 samples of patients undergoing elective laparotomy due to ovarian tumor. We compared the sensitivity and specificity between mesothelin and Ca-125, then the data were analyzed using SPSS software version 22.0. Result: According to the ROC curve analysis, optimal sensitivity and specificity value of mesothelin was 63.2% and 54.5% at a cut-off point of 0.45 pg/ml; or 42.1% and 72.7% at a cut-off point of 0.55 pg/ml. While the value of both optimal sensitivity and specificity of Ca-125 was 73.7% and 63.6% at a cut-off point of 46.63 U/ml. Conclusion: Mesothelin and Ca-125 are not different significantly for the AUC value of 50%. Due to higher sensitivity and specificity of Ca-125 than mesothelin, Ca-125 is still used as tumor marker for screening the ovarian malignancy. [Indones J Obstet Gynecol 2016; 4-2: 107-110] Keywords: Ca-125, mesothelin, ovarian malignancy